Joint kinematics and inter-segmental coordination during underwater undulatory swimming: Comparing swimmers of different performance levels - Yamakawa, Keisuke K.; Nakazono, Yusaku; Arellano, Raúl; Ruiz-Navarro, Jesús J.; Sengoku, Yasuo; Takagi, Hideki (Journal of biomechanics, 2026)
•Higher-performance swimmers showed greater velocity in both kick phases, especially during the upward kick.•During the late downward kick, high-performance swimmers maintained greater shoulder extension to reduce drag.•During the upward kick, high-performance swimmers showed larger peak knee extension and greater lower-trunk flexion.•Higher-performance swimmers were characterised by a coordination of the arms, lower trunk and thighs that reduced resistance. This study aimed to elucidate the relationship between performance in underwater undulatory swimming (UUS) and joint kinematics as well as intersegmental coordination. Thirty-one swimmers performed two 15 m UUS trials with maximum effort, and two-dimensional full-body kinematics were recorded using a camera. Twenty-four participants were categorised into higher- and lower-performance groups based on their UUS performance (n = 9 and n = 15, respectively) according to specific inclusion criteria. Time-series data of swimming velocity and joint and segmental angles were compared using statistical parametric mapping (SPM) for continuous analysis. A kinematic synergy analysis was conducted to extract intersegmental coordination patterns from a single cycle of UUS movement. The SPM analysis revealed that the higher-performance group achieved greater swimming velocity during specific phases of both downward and upward kicks, with a longer period of difference in the upward kick phase. This result highlighted that attaining greater velocity during the upward kick is important for better UUS performance. The higher-performance group also exhibited greater shoulder motion during the downward kick, a larger maximal knee extension angle, and greater trunk movement during the upward kick. Furthermore, the difference in trunk motion was mainly attributed to variations in lower trunk movement. Kinematic synergy analysis indicated that two primary synergies predominantly contributed to UUS movement in both groups; however, coordination patterns involving the arm, lower trunk, and thighs differed between groups. These findings suggest that swimmers with higher UUS performance regulate shoulder and lower trunk movements to maintain an upper body position that minimises water resistance.